The Banking Sector under Financial Stability - Ramlall, Indranarain (Theory and Practice of Financial Stability Ser., 2018)
The Banking Sector Under Financial Stabilityrecognises the critical importance of the banking sector with respect to financial stability risks, and considers the unique position of banks which by nature assume higher risks, existing within a low equity to total assets ratio.